Entry mode choice and market selection of born globals in developing countries: a multiple-case study of the ecuadorian software sector - Salazar, María Alejandra Calvache (2016)
The 'Born Global' phenomenon refers to companies that regard the global market as their natural context and that start their internationalization process very early after inception. Traditional theories like the Uppsala model no longer can explain this process. Therefore, other theories have been emerging, such as the network perspective. There are some studies related to this field, mainly performed in developed countries with small markets and open economies. However, very few studies have been done in developing economies. Moreover, there are limited researches regarding the choice of entry mode and market selection of born global firms. Consequently, this study pretends to describe the main factors influencing the choice of entry mode and market selection of born global companies from developing economies. The focus of the research is the software industry and a multiple case study was performed to three companies in Ecuador. The methodology included in-depth interviews to founders as well as collection of secondary data. Drawing from empirical evidence, it was found that the main factors influencing entry mode choice are financial constraints, expected revenues, internationalization speed, niche markets and previous business experience of founders. On the other hand, market selection is influenced by similarities in language and culture, niche markets and network relations.